BY THE 115TH ANNIVERSARY OF THE FOUNDING OF THE DEPARTMENT OF HISTOLOGY, CYTOLOGY AND EMBRYOLOGY ODESSA NATIONAL MEDICAL UNIVERSITY - Breus, V.E.; Ulyanov, V.A.; Kuvshinova, I.I.; Tiron, O.I. (World of Medicine and Biology, 2015)
The article presents a brief historical data about the formation of the Department of Histology, Cytology and Embryology Odessa National Medical University. The department was founded in 1900, since the opening of the Faculty of Medicine at the Novorossiysk University. It was the 4th Histology Department in Ukraine (Kharkiv – 1867, Kiev – 1868, Lviv – 1895). The first Head of department (in 1900–1902) Vladimir Valerianovich Podvysotsky (1857–1913) organized the Faculty of Medicine and was its first Dean. His research interests was unusually wide: the microscopic structure of glandular epithelium and its regeneration in normal conditions and in pathology, etiology and pathogenesis of tumors, bacteriology and immunity problems, the organization of health care, scientific management of balneology society. Over the years, the department was headed by Professor A.F. Mankovsky (1902–1917), V. Voronin (1917–1918), D.K. Tretyakov (1918–1919), Janiszewski V.E. (1919–1920), F.N. Zhmaylovich (1920–1923), M.N. Zaevloshin (1923–1944), B.I. Kardasevich (1944–1946, 1950–1954), V.V. Averburg (1946–1950), S.D. Shahov (1954–1958), N.D. Zaitsev (1958–1976), V.F. Pchelyakov (1976–1993), V.K. Naphanyuk (1993–2006). Currently, the department headed by Professor Vadim Ulyanov. Scientific direction of the department to study the morphogenesis of epithelial and connective tissue in physiological and pathological conditions; the study of the biological effects of nanoscale materials. Employees of the department in 2012, participated in the creation of a new section "Structural and Functional Nanomaterials for medicine" Scientific Council for new materials to the Committee of Natural Sciences International Association of Sciences Academies and the Paton Electric Welding Institute of NAS of Ukraine.